Fabrication and Characterization of n-ZnO/n-Si Heterojunction - Chao Xiong; Weihong Li; Hailin Xu; Lei Chen; Hongchun Yuan; Xifang Zhu; Yan Zhang; Xiangcai Zhou (Institute of Advanced Engineering and Science, 2013)
The n-ZnO/n-Si heterojunction are fabricated by depositing ZnO films on n-Si (111) films substrate using magnetron sputtering Al doped ZnO ceramic target. The structures of n-ZnO films, analyzed by X-ray diffraction (XRD) spectroscopy, and the preferential orientation of the ZnO grains is observed along the (101) and (100) axis aligning with the growth direction. The photoelectric properties, charge carrier transport properties and conductive mechanism were studied by testing the I-V, C-V characteristics with illumination and without illumination. Current-voltage (I-V) measurements of n-ZnO/n-Si heterojunctions show good diode characteristics and photovoltaic effects with illumination. The forward conduction is respectively determined by carrier recombination in the space charge region, defect-assisted tunneling and exponential distribution trap-assisted space charge limited current mechanism with the increase of forward voltage. Also, a band diagram of n-ZnO/n-Si heterojunctions has been proposed to explain the transport mechanism. As the conduction band and valence band offset in the ZnO/n-Si heterojunction is too big, the current transport mechanism is dominated by the space-charge limited current (SCLC) conduction at the forward voltage exceed 0.8 V. The results suggest the existence of a large number of interface states in ZnO/n-Si heterojunction, and the interface states can be reduced and the photoelectric properties can be further improved. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3268